2016
DOI: 10.31768/2312-8852.2016.38(1):22-25
|View full text |Cite
|
Sign up to set email alerts
|

CD40/CD40 LIGAND INTERACTIONS AND TNFα TREATMENT REDUCE ACTIVITY OF P105 PROMOTER OF THE HUMAN PAPILLOMA VIRUS-18 IN VITRO

Abstract: Background: Cervical carcinoma cells including those infected with the oncogenic human papilloma virus (HPV) and several cervical carcinoma cell lines show a strong expression of the CD40 receptor, unlike benign cervical epithelial cells infected with HPV. The functional relevance of this up-regulated expression in the tumor is not fully understood. Nevertheless, it might offer a unique possibility to target those malignant cells due to the antiviral and antitumoral effects of the CD40/CD40 ligand (CD40L) inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…CD40/CD40L interaction is a central signalling pathway for dendritic maturation and for inducing CD4 + and CD8 + responses during HPV chronic infection [ 67 ]. In a HeLa model of cervical carcinoma study, , this interaction was able to repress transcriptional activity of HVP18-P105 promoter and increase IL-6 synthesis [ 68 ]. Thus, therapeutic approaches were developed/tested (e.g.…”
Section: Dendritic Cells and Immune Checkpoint Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…CD40/CD40L interaction is a central signalling pathway for dendritic maturation and for inducing CD4 + and CD8 + responses during HPV chronic infection [ 67 ]. In a HeLa model of cervical carcinoma study, , this interaction was able to repress transcriptional activity of HVP18-P105 promoter and increase IL-6 synthesis [ 68 ]. Thus, therapeutic approaches were developed/tested (e.g.…”
Section: Dendritic Cells and Immune Checkpoint Moleculesmentioning
confidence: 99%
“…clinicaltrials.gov identifier NCT00319748) or are under clinical trials (e.g. NCT03418480) to induce the activation of this pathway aiming the prevention of hrHPV genes expression and promotion of higher CD4 + and CD8 + responses [ 68 , 69 ].…”
Section: Dendritic Cells and Immune Checkpoint Moleculesmentioning
confidence: 99%
“…These findings were further confirmed by Huang Q et al [ 29 ]. In vivo studies have shown that the expression of CD40 is correlated with HPV positivity, vascular endothelial growth factor (VEGF) expression, and microvessel density [ 27 , 30 ]. In recent years, various studies have shown that CD40 gene polymorphisms are related to some malignant tumors, such as non-Hodgkin’s lymphoma [ 31 ], breast cancer [ 32 ], and lung cancer [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%